Rational treatment for vulvovaginal candidiasis caused by resistant Candida species - G.B. Dikke (LCC «Medicine-Inform», 2019)
G.B. Dikke F.I. Inozemtsev Academy of Medical Education, St. Petersburg, Russian Federation In recent decade, growing incidence (24-29%) of vulvovaginal candidiasis caused by Candida non-albicans is reported. Candida species are characterized by reduced (on average, 2-fold) sensitivity to azoles and cross-resistance. Differential treatment strategy choice for vulvovaginal candidiasis depends on clinical variant (acute or recurrent) and etiological agent (identification of Candida species by culture). In vulvovaginal candidiasis caused by Candida non-albicans or azole-resistant Candida albicans (including vulvovaginal candidiasis in pregnant and nursing women), polyene antibiotic (i.e., natamycin) should be prescribed. The efficacy of the treatment of acute non-complicated vulvovaginal candidiasis with vaginal natamycin (100 mg daily) is 67-85% for 3 day-treatment and 86-95% for 6-day treatment. Natamycin (100 mg vaginally for 6 to 12 days) is first-line therapy for recurrent vulvovaginal candidiasis caused by Candida non-albicans. Treatment efficacy for a certain episode is 88-94%. Proceeding with treatment for six months (100 mg weekly) prevents recurrences in 98% of women. In pregnant women, natamycin results in clinical recovery during the whole pregnancy and promotes decreased rate of pregnancy complications. Keywords: vulvovaginal candidiasis, Candida albicans, Candida non-albicans, biofilm, recurrence, pregnancy, antifungal treatment, natamycin, Primafungin. For citation: Dikke G.B. Rational treatment for vulvovaginal candidiasis caused by resistant Candida species. Russian Journal of Woman and Child Health. 2019;2(3):187-193.